Comparing psychopathological symptoms in portuguese football fans and non-fans - Leite, Ângela (2020)
The present study aims to characterize football fans and non-fans and to compare their psychopathological symptoms with the latest normative values for the Portuguese population from Canavarro in 2007. Results showed that football fans and non-fans are mostly male, have an affective relationship, are childless, have secondary education or a high degree, and are employed or students; fans are more likely to be male, dating, unemployed, to have elementary education and be younger than non-fans. Football fans present significantly higher psychopathological symptoms than non-fans in somatization, interpersonal sensitivity, anxiety, hostility, paranoid ideation and psychoticism and all psychopathological indexes. Football fans present values very close to those of populations with emotional distress in hostility and are above the mean of the general population in obsession–compulsion, hostility, paranoid ideation and psychoticism.